Pengaruh Gaya Kepemimpinan Dan Motivasi Terhadap Kinerja Pegawai Politeknik Ilmu Pelayaran Semarang Dengan Dimediasi Kepuasan Kerja Pegawai - Arief Nashrul Firdani; Alimuddin Rizal (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2023)
This study aims to examine and analyze the effect of leadership style and work motivation on the performance of Semarang Service Science Polytechnic employees mediated by job satisfaction. Quantitative descriptive method was used in this study, with a population of 218 employees of the Semarang Shipping Science Polytechnic. The research was carried out using validity test analysis, reliability test, and model test which included regression test, coefficient of determination test, simultaneous significance, and mediation test using SPSS 21.0 software. From the results of this analysis and discussion, it shows that leadership style has a positive but not significant effect on the job satisfaction of Semarang Shipping Polytechnic employees, while work motivation has a positive and significant influence on job satisfaction and performance of Semarang Shipping Polytechnic employees, but leadership style does not influential and significant employee performance, while job satisfaction has a positive but not significant effect on the performance of employees of the Semarang Shipping Science Polytechnic.